Shadows, Specters, Shards : Making History in Avant-Garde Film - Skoller, Jeffrey (Book collections on Project MUSE., 2005)
Shadows, Specters, Shards examines experimental films, including work by Eleanor Antin, Ernie Gehr, and Jean-Luc Godard, that take up events such as the Holocaust, Latin American independence struggles, and urban politics. In his discussion of avant-garde film of the 1970s, 1980s, and 1990s, Jeffrey Skoller reveals how a nuanced understanding of the past is linked to the artistry of image making and storytelling.